Effect fix drag-reducing on blades to performance of savonius wind turbine. Issue 1 (February 2020) - Siregar, I H; Effendy, M; Rasyid, A H A
Abstract: This article proposes a design model for vertical axis wind turbines based on drag forces by adding fix drag-reducing to the blades tested by subsonic wind tunnel with wind speeds of 3-6 m/s and opening angle variations of fix drag-reducing from 0, 15, 30 and 45°. The research explained that at the opening angle of 15° can improve the performance of the wind turbine model significantly at high wind speeds on the contrary for larger angle openings. The addition of fix drag-reducing instead reduces the performance of the wind turbine model considerably on all variations of wind speed tested.